1996
DOI: 10.1364/ol.21.001277
|View full text |Cite
|
Sign up to set email alerts
|

Competition between two lasing modes of Sulforhodamine 640 in highly scattering media

Abstract: Two lasing modes are observed for Sulforhodamine 640 in highly scattering media pumped by 3-ns 532-nm laser pulses. The stimulated-emission thresholds are found to depend on both concentration of laser dye and scattering particle density. At 2.5 x 10(-2) M dye solution with TiO(2) scattering nanoparticles from 5 x 10(9) cm(-3) to 10(11) cm(-3), the thresholds are found to decrease by more than 2 orders of magnitude. The dominating lasing modes are found to switch from 650 to 620 nm with the increase of density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…6,7 In a high dye concentration sample, bichromatic emission has been observed. 8,9 Powder lasers display similar phenomena. Gouedard et al reported the multipulsing behavior in hydrated neodymium chloride powder, which is similar to the relaxation oscillation in a conventional cavity laser.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…6,7 In a high dye concentration sample, bichromatic emission has been observed. 8,9 Powder lasers display similar phenomena. Gouedard et al reported the multipulsing behavior in hydrated neodymium chloride powder, which is similar to the relaxation oscillation in a conventional cavity laser.…”
Section: Introductionmentioning
confidence: 84%
“…After Lawandy et al reported the random laser, many experimental and theoretical studies have been reported. [6][7][8][9] The dependence of spectral and temporal characteristics of the random laser on dye concentration and density of scattering particles have been studied. 6,7 In a high dye concentration sample, bichromatic emission has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…One of these systems consisting of optically pumped solutions of Rhodamine 640 in methanol with TiO 2 particles presents a peculiar feature: the appearance of bichromatic emission, with well-defined wavelength peaks. 6,7 Detailed experimental works on this subject were carried out by Sha et al 8,9 Based on their experiments, the spectral properties as a function of the scattering particle density, dye concentration, and pump energy were studied. In recent experiments, the radiation peaks with narrow linewidth can be observed in the random media that is combined with liquid crystal and dye.…”
Section: Introductionmentioning
confidence: 99%
“…Random lasing in disorder media is of significance for both fundamental research and technological applications. In the past four decades, great research efforts have been expended in the field [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . Lasing phenomenon has been found in few materials [1][2][3][4][5] , such as dye solutions; dye doped solid polymer matrices; laser crystal powders, and others.…”
mentioning
confidence: 99%
“…One of these systems consisting by optically pumped solutions of Rhodamine 640 in methanol with TiO 2 particles presents a peculiar feature: the appearance of bi -chromatic emission, with well defined wavelength peaks. Detailed experimental works on this subject were carried out by Sha et al [6][7] . Based on their experiments, the spectral properties as a function of the scattering particle density, dye concentration, and pump energy were studied.…”
mentioning
confidence: 99%